Bridging the divide: analysing disparities in drinking water services between urban and rural areas in Lilongwe, Malawi—implications for water justice and infrastructure equity - Chimombo, Masautso Joseph (Frontiers in Water, 2025)
IntroductionMost studies on water justice and rural–urban divide in drinking water services coverage have been done at national scale. Such nationwide studies often mask injustices and differences happening at the sub-national and community levels.MethodsEmploying infrastructure violence as a theoretical framework and a mixed methods case study design, the study was carried out in Lilongwe to assess the extent of injustices in drinking water coverage and drinking water service levels in Lilongwe in Malawi. Service coverage was assessed on access, affordability, and reliability.Results and discussionThe study reveals that disparities between Lilongwe urban and Lilongwe rural in drinking water coverage and service levels are wider than nationwide studies reveal. Lilongwe urban households have higher access to safe drinking water than rural households. Rural residents suffer the most from the pain of infrastructure violence caused by their exclusion from the centralised piped water infrastructure network. Therefore, deliberate interventions to improve drinking water services in rural areas of Malawi are critically needed. Investing in affordable and easy to manage sustainable water supply systems like solar powered water pumping systems and rainwater harvesting can go a long way in moving rural communities up the water service ladder. Further, empowering rural communities with finances and skills for repairing boreholes can reduce the proportion of boreholes which are nonfunctional which currently stands at 30%.